Forms of social and spatial differentiation in towns (based on the case of Maribor) - Drozg, Vladimir (Journal for Geography, 2012)
This contribution discusses forms of spatial differentiation of the town, occurring while human needs are being fulfilled (social connections, supply, culture, education and recreation). Social and spatial differentiation is most noticeable in the area of social connections, clothing stores and culture. The most important social characteristics, responsible for spatial differentiation are age and material situation. Also, the size of the town proved to be crucial for social and spatial differentiation.
Keywords: social differentiation; spatial differentiation; Maribor